The Effectiveness of The Handwashing Program with Soap (CTPS) In Preventing E. Coli Contamination on Elementary School Student, West Martapura South Kalimantan - Mutttaqien, Fauzan; Khatimah, Husnul; Fakhrurrazy, Fakhrurrazy; Arganita, Fidya Rahmadhany; Maulana, Irfan; Yuliana, Ida (Fakultas Kedokteran Universitas Lambung Mangkurat, 2024)
Martapura river had been discovered of indicators of microbial contamination of drinking water, namely total coliform and E coli which are harmful to health. CTPS program for elementary schools in West Martapura sub-district has been going for long time to prevent disease. Tihis study aimed to know the difference in the effectiveness of using Martapura river water for CTPS in elementary school children in Martapura Barat District to preventing E. Coli contamination. The research method used the true experiment method with a posttest only control group design research design. The research group named group (P1) CTPS using processed Martapura river water, group with hand washing soap (P2) CTPS using Martapura river water without being processed and group (K) CTPS with PDAM water . The research subjects were18 elementary student selected by simple random sampling technique. The object study was the observation of the presence of Escherichia coli bacteria which were found from the hand swabs of elementary school children in West Martapura sub-district whose schools had treated water facilities and did not have treated water facilities. Also taking palm swabs for the research subjects, a quality test for PDAM water, Martapura river water and processed river water at the three elementary schools was carried out and examined at the Banjarbaru BBTKL-PPB Laboratory. The results showed that for CTPS water samples from PDAM water sources only counted 1 CFU E coli/100 ml, while CTPS water from the Martapura River and PAMSIMAS the number of E. coli colonies was > 200 CFU/100 ml. For all samples of palm swabs from the elementary school students, all results were negative for E. Coli CFU / cm2. The conclusion is that there is no difference in the effectiveness of using Martapura River water, both treated and untreated, in the CTPS program in reducing E.Coli numbers.